Dynamic System Model Using the Combi (Communication for Behavioral Impact) Method Approach to Early Detection of Stunting Neonates in Pregnant Women North Sumatra - Amirah, Asriwati; Suharto, Teguh; Renowening, Yuniars; Noviati, Titik Dwi; Ridha, Alfan; Ulaa, Mar'atun (Poltekkes Kemenkes Palu, 2024)
This study addresses the persistent nutritional challenge of stunting in Indonesia, often misconceived as solely hereditary. Research indicates that genetic factors contribute only 15%, emphasizing the significance of nutritional intake, growth hormones, and maternal and toddler health in stunting. The research aims to identify and prevent early stunting in neonates, aligning with the government's goal to combat stunting by 2025. Using an observational research design and dynamic system modeling through Stella software, the study develops an effective strategy model for reducing stunted neonates in the future. Simulation experiments provide reliable insights into dynamic systems, predicting various scenarios based on input data. Results highlight the importance of enhancing Antenatal Care (ANC) standards, iron supplementation, additional nutrition, and effective case management for pregnant women. Implementation of these factors at low to medium levels could potentially reduce stunted neonates by 25%, reaching 44% at a high level compared to current conditions. The study further recommends an empowerment model for pregnant women, involving family assistance in managing highly nutritious food based on local wisdom. This holistic approach addresses the root causes of stunting, contributing to the success of stunting prevention programs in Indonesia. The research emphasizes the multifactorial nature of stunting and provides valuable insights for policymakers and healthcare practitioners to develop comprehensive strategies for effective intervention and prevention.